A Modular Approach of Different Geometries for Non‐invasive Oxygen Measurement inside Moving Food Packages. Issue 4 (28th February 2017) - Cocola, L.; Fedel, M.; Tondello, G.; Poletto, L.
Abstract : The importance of a controlled atmosphere in food packages is paramount to maximize shelf life, limit bacterial activity and avoid mould growth. Residual oxygen is one of the most important gases related with ageing of products meant to have a long shelf life. As oxygen is a main component in the atmosphere, it can be present in foods after manufacturing and usually needs to be removed during the packaging process. An experimental set‐up for non‐invasive gaseous oxygen sensing inside food packages using laser spectroscopy has been studied in order to easily adapt the measurement technique on a wide range of trays with different geometrical and optical properties. Different measurement arrangements have been considered and evaluated in order to provide guidelines to the applicability of this system to samples in a continuously moving production line. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : In this work, an experimental set‐up for measuring residual oxygen inside modified atmosphere packages through tunable diode laser absorption spectroscopy has been used to evaluate the applicability of this method on a range of package styles and contents with different optical properties. Different measurement arrangements have been pointed out and evaluated in order to provide some guidelines to the suitability of this method on a continuously moving production line.